Isolation and partial characterization of a geminivirus causing bean dwarf mosaic - Morales, F; Niessen, A; Ramírez, B.; Castaño, M. (Scientific Societies, 1990)
Bean dwarf mosaic virus (BDMV) was transmitted mechanically and by the whitefly Bemisia tabaci from and to susceptible bean (Phaseolus vulgaris) cultivars. Two species of Sida, suspected weed reservoirs of BDMV, were also shown to be susceptible hosts by whitefly transmission tests. Electron microscopy of ultrathin sections of BDMV-infected bean and Sida sp. leaf tissue revealed the presence of viruslike particle aggregates in phloem cells. Quasi-isometric nucleoprotein particles (A260/280nm = 1.4), found predominantly in pairs measuring about 20 × 33 nm, were isolated from BDMV-infected bean plants. Purified nucleoprotein was infective to Topcrop bean plants, inducing characteristic bean dwarf mosaic symptoms. Dissociated infectious nucleoprotein yielded a single protein species of molecular mass 27,500 daltons and a single nucleic acid band of approximately 2.6 kb. Purified nucleic acid was resistant to RNase but sensitive to DNase 1 and nuclease S1, indicating the presence of single-stranded DNA. The isolated virus was serologically related to African cassava mosaic, bean golden mosaic, mung bean yellow mosaic, and tomato golden mosaic viruses. Bean dwarf mosaic virus is proposed to be a new member of the geminivirus group.